Antibodies against angiotensin II receptor type 1 and endothelin A receptor are increased in COVID-19 patients - Miedema, Jelle R.; Janssen, Matthijs L.; Thüsen, Jan von der; Endeman, Henrik; Langerak, Anton W.; Hellemons, Merel E.; van Nood, Els; Peeters, Bas W. A.; Baart, Sara J.; Schreurs, Marco W. J. (Frontiers in Immunology, 2023)
Increased titers of autoantibodies targeting the G protein-coupled receptors angiotensin II type 1 receptor (AT1R) and endotelin-1 type A receptor (ETAR) are associated with severe COVID-19 infection.The aim of this study was to determine whether 1) these antibodies are specifically related to COVID-19 disease pathogenesis or increased during any severe respiratory illness, 2) if they are formed during illness and 3) if they correlate with inflammatory markers or long term symptoms.Antibodies against AT1R, ETAR and antinuclear antibodies (ANA) were measured in n=40 prospectively enrolled COVID-19 patients and n=207 COVID-19 patients included in our biobank. Clinical and laboratory findings were prospectively and retrospectively assessed in both cohorts and results were combined for analysis. The presence of auto-antibodies against AT1R or ETAR in peripheral blood was compared between hospitalized patients with COVID-19 and controls (n=39). Additionally, AT1R and ETAR titers were compared between patients with an unfavourable disease course, defined as intensive care admission and/or death during hospital admission (n=121), to those with a favourable disease course (n=126). A subset of intubated patients with severe COVID-19 were compared to intubated patients with ARDS due to any other cause.Significantly increased AT1R and ETAR antibody titers were found in COVID-19 patients compared to controls, while titers were equal between favorable and unfavorable COVID-19 disease course groups.On ICU, intubated patients with COVID-19 had significantly increased AT1R and ETAR titers compared to patients with ARDS due to any other cause. The titers did not correlate with baseline inflammatory markers during admission or with diffusion capacity, cognitive impairment or fatigue measured at three months follow-up .In patients hospitalized for COVID-19, antibodies against AT1R and ETAR are increased compared to controls and patients with ARDS due to other causes than COVID-19. The baseline antibody titers do not correlate with inflammatory markers or long term symptoms in this study.